2014
DOI: 10.1093/hmg/ddu194
|View full text |Cite
|
Sign up to set email alerts
|

Rapid depletion of muscle progenitor cells in dystrophic mdx/utrophin−/− mice

Abstract: Duchenne muscular dystrophy (DMD) patients lack dystrophin from birth; however, muscle weakness becomes apparent only at 3-5 years of age, which happens to coincide with the depletion of the muscle progenitor cell (MPC) pools. Indeed, MPCs isolated from older DMD patients demonstrate impairments in myogenic potential. To determine whether the progression of muscular dystrophy is a consequence of the decline in functional MPCs, we investigated two animal models of DMD: (i) dystrophin-deficient mdx mice, the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 75 publications
7
60
0
2
Order By: Relevance
“…To determine if the mNKO myopathy worsened over time, as occurs in severe muscular dystrophies (Lu et al, 2014; Sacco et al, 2010), we monitored body weight and endurance as the animals aged. Though equal tibia lengths indicated that mutants were skeletally full grown (Figure S2B), the slight decrease in lean mass observed in 3-month-old male knockouts represented the beginning of a plateau in this parameter, driving a divergence in body weight as control littermates continued to gain weight (Figure 2D, E).…”
Section: Resultsmentioning
confidence: 99%
“…To determine if the mNKO myopathy worsened over time, as occurs in severe muscular dystrophies (Lu et al, 2014; Sacco et al, 2010), we monitored body weight and endurance as the animals aged. Though equal tibia lengths indicated that mutants were skeletally full grown (Figure S2B), the slight decrease in lean mass observed in 3-month-old male knockouts represented the beginning of a plateau in this parameter, driving a divergence in body weight as control littermates continued to gain weight (Figure 2D, E).…”
Section: Resultsmentioning
confidence: 99%
“…Impairment in dystrophin and its associated proteins causes an interruption between the myofiber, its sarcolemma, and the ECM, leading to altered mechanical stress, reduced stiffness, inflammation, and consequent muscle regeneration . Transgenic mouse models for DMD ( mdx , mdx /mTR, mdx / utrophin −/− ) have defined the phenotype of muscle dysfunction in DMD and have been used to evaluate the role of SCs in the progressive weakness associated with DMD . Sacco et al .…”
Section: Cerebral Palsy and Muscular Dystrophymentioning
confidence: 99%
“…107,108 Transgenic mouse models for DMD (mdx, mdx/mTR, mdx/utrophin 2/2 ) have defined the phenotype of muscle dysfunction in DMD and have been used to evaluate the role of SCs in the progressive weakness associated with DMD. 109 Sacco et al 110 showed that pathological muscle progression in DMD could be related to inability of the SCs to maintain the capacity to repair after multiple damage-repair cycles, specifically early exhaustion of the stem cell pool. Consistent with the idea that dystrophic muscle undergoes multiple cycles of regeneration, it has been shown that telomere shortening 110 occurs in DMD patients' muscles.…”
Section: Cerebral Palsy and Muscular Dystrophymentioning
confidence: 99%
“…Essa linhagem de camundongos foi gerada por dois grupos, de forma independente, com o intuito de verificar a hipótese de que a compensação da distrofina pela utrofina nos camundongos mdx poderia ser a responsável por proporcionar o fenótipo mais leve da doença nestes animais (Deconinck et al 1997;Grady et al 1997 (Lu et al 2014) e também aprofundaram o conhecimento sobre a gravidade das deformações nos tecidos musculoesqueléticos, como osso e cartilagem (Isaac et al 2013), observações consistentes com as alterações em pacientes com DMD.…”
Section: Modelos Animaisunclassified
“…Apesar de termos confirmado o resultado anterior utilizando pericitos de tecido adiposo de outra doadora, já foi mostrado que existem subpopulações diferentes de pericitos (Birbrair et al 2013;Birbrair et al 2014): uma população com potencial miogênico e angiogênico e outra com potencial de formação de fibrose. Além disso, mostrou-se que o ambiente muscular que receberá as células também é importante, pois quanto mais velho e lesionado, pior a eficiência das células transplantadas (Birbrair et al 2013;Lu et al 2014). …”
Section: Avaliação Do Potencial Terapêutico De Ctas E Pericitosunclassified